The Dawning of the Stream of Aquarius in RAVE - Williams, M; Steinmetz, M; Sharma, S; Bland-Hawthorn, J; Jong, R; Seabroke, G; Helmi, A; Freeman, K; Binney, J; Minchev, I; Bienaymé, O; Campbell, R; et al. (Institute of Physics Publishing, 2010)
We identify a new, nearby (0.5 < d < 10 kpc) stream in data from the RAdial Velocity Experiment (RAVE). As the majority of stars in the stream lie in the constellation of Aquarius we name it the Aquarius Stream. We identify 15 members of the stream lying between 30 < l < 75 and -70< b <-50, with heliocentric line-of-sight velocities V_los~-200 km/s. The members are outliers in the radial velocity distribution, and the overdensity is statistically significant when compared to mock samples created with both the Besançon Galaxy model and newly-developed code Galaxia. The metallicity distribution function and isochrone fit in the log g - T_eff plane suggest the stream consists of a 10 Gyr old population with [m/H]~-1.0. We explore relations to other streams and substructures, finding the stream cannot be identified with known structures: it is a new, nearby substructure in the Galaxy's halo. Using a simple dynamical model of a dissolving satellite galaxy we account for the localization of the stream. We find that the stream is dynamically young and therefore likely the debris of a recently disrupted dwarf galaxy or globular cluster. The Aquarius stream is thus a specimen of ongoing hierarchical Galaxy formation, rare for being right in the solar suburb.